Job burnout: does it influence employees to leave? / Roseamilda Mansor... [et al.] - Mansor, Roseamilda; Azhar, Nor Ananiza; Hassan, Nur Diana (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
The aim of this study was to study the relationship between job burnout and employee’s intention to leave. The study was conducted at a company in northern Malaysia to determine the most dominant factor that contributes to the employees’ intention to leave. Job burnout derives from three key dimensions; emotional exhaustion, depersonalization and lack of accomplishment. Burnout will lead employees’ tendency to absent then reduced productivity and increased turnover. Probability sampling method was used in this study and a survey questionnaire was adopted. The questionnaire was developed using five point Likert scales and distributed to non-executive level. Statistical Package for the Social Sciences (SPSS) was used for data analysis based on 108 completed and usable questionnaires. Descriptive analysis used to investigate users’ demographic information. The results showed that emotional exhaustion and lack of accomplishment to be positively significant with employees’ intention to leave. Thus, employees responded negatively that they will leave the organization even they are suffering from depersonalization.